The good executive in the wake of COVID-19: using story completion to study the rise and development of alternative selves - Manca, Claudia; Russo, Marcello; Leone, Ludovica; Gaavar, Richa (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic was a turning point that had the potential to shape how individuals manage their work-family interface, possibly bringing the emergence of alternative self-definitions that are tied to changing cultural norms. This study aims to explore whether and how executive managers have developed an alternative self after the pandemic, shedding light on the interplay between cultural norms, gendered assumptions, and executive identity formation.MethodsTo understand the development of self-concept as intertwined with cultural norms and gendered assumptions, we used the story completion method that requires participants to create autonomous stories based on a provided “cue.” We analyzed stories written by 32 executives based in Italy and the United Kingdom (14 males and 18 females) who reflected upon contemporary discourses on what it takes to be a good executive when the scaffolding between work and family life has been disrupted.FindingsThis study highlights that the pandemic has served as a turning point that elicited alternative views about self and cultural meanings for the executives. These alternative views trigger three distinct patterns for the development of alternative selves i.e., becoming a work-life balance advocate, becoming a family man, and reasserting the ideal worker.DiscussionThis study sheds new light on the dynamics at the intersection between individual experiences in work and family management and broader societal expectations and cultural norms. It highlights how executives adapt their self-concept in response to major turning points, and how cultural norms conflate into this process. This allows us to offer new insights into the relationship between turning points, identity shifts, and societal expectations.